Merajut Ummatan Waasathan di tengah Pandemi menuju Ukhuwah Wathoniyah - Devi Eka Yulita Br. Tarigan; Hasrat Efendi Samosir (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2020)
The purpose of this paper is to find out how to knit the wasathan ummatan in the midst of a pandemic towards ukhuwah wathoniyah. The approach used in this paper uses a library research method or approach, while data collection is done by examining, collecting and exploring several books, journals, related information from print and electronic media, as well as things that are considered relevant to the writing. The findings of this paper are to know how to knit a wasathan ummatan (middle), that is, to become a personal mediator in the midst of a pandemic, by not becoming a proponent and confusing the atmosphere that results in the disruption of this nation. The method that is taken to create national harmony starts with yourself, by becoming a person / middle ummat (wasathan), after you are tidied up, it will affect the environment that makes the nation's life harmonious even in the midst of a pandemic, by taking the steps described in the writing this so that the creation of ukhuwah wathoniyah (fellow countrymen)